Answer:
x = 3, -2
Explanation:
To help us factor, we can split the middle term up into the sum of the terms -3x and 2x:
![x^2+(-3x)+2x-6=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2ccz59vm45p1rywkysmsciy0ejx0kblfp7.png)
From there, we can factor out an x from the first two term and a 2 from the last two to obtain the equation
![x(x-3)+2(x-3)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8sm8bbo6gip8g7vljst53gl3aa027wj27z.png)
Factoring out an (x - 3) from each term gives us the equation
![(x-3)(x+2)=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/2d51j5xl9gvwhzqk7lw69bssn6d44gkz2t.png)
At this point, we can divide by either x - 3 or x + 2 to obtain the two equations
and
![x+2=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ofuzuzxy51s3qran6lig4fpglhv6g1c3g7.png)
Solving both for x gives us the solutions x = 3 and x = -2. We can verify these by substituting them back into the original equation:
![3^2-3-6=0\\9-3-6=0\\6-6=0\\0=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3sdqnj8hf3jrceu7vs7jiwdl4143ppv2cj.png)
![(-2)^2-(-2)-6 = 0\\4+2-6=0\\6-6=0\\0=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/av2n3xau7xk8pt838alt7a1oajyxuhb1l6.png)